GEOAM: A Holistic Assessment Tool for Unveiling the Geoeducational Potential of Geosites - Zafeiropoulos, George; Hara Drinia (Geosciences, 2023)
A new assessment method named GEOAM (geoeducational assessment method), that will be a useful tool for highlighting the geoeducational and geoethical value of a geosite, is proposed. This method takes into account, initially, 11 criteria, which are grouped into 8 categories. Each criterion addresses a different aspect of the geosite’s potential for promoting sustainable development, environmental management, and education. A simplified scoring system using a scale of 1–5 is used, where each criterion is scored based on the degree to which it is presented or implemented. The method was piloted in eight geotopes of the Kalymnos Island and five geotopes of the Nisyros Island, in the SE Aegean Sea, Greece. The implementation of this assessment method highlighted the geoeducational value of these geosites. Based on the criteria and subcriteria incorporated in GEOAM, this paper discusses GEOAM’s potential to promote sustainable development and rational environmental management by directing educators and stakeholders toward actions that conserve and protect geoheritage for future generations, while also contributing to the economic, social, and cultural development of the surrounding communities. By quantifying the geoeducational potential of geosites and integrating essential concepts such as geoconservation and geoethics, the implementation of this new assessment method can benefit the educational community, tourism industry, and environmental conservation efforts.